2015
DOI: 10.2478/sgem-2014-0031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Model Tests of SDP and CFA Pile Groups in Non-Cohesive Soil

Abstract: The research topic relates to the subject of deep foundations supported on continuous flight auger (CFA) piles and screw displacement piles (SDP). The authors have decided to conduct model tests of foundations supported on the group of piles mentioned above and also the tests of the same piles working as a single. The tests are ongoing in Geotechnical Laboratory of Gdańsk University of Technology. The description of test procedure, interpretation and analysis of the preliminary testing series results are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Preliminary tests have shown that in the case of pile groups, where the loads on pile heads can act eccentrically, single gauge sensor readings do not lead to correct results (Krasiński and Kusio [4]). To avoid errors in measurement, two types of sensors were prepared.…”
Section: The Construction Of Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary tests have shown that in the case of pile groups, where the loads on pile heads can act eccentrically, single gauge sensor readings do not lead to correct results (Krasiński and Kusio [4]). To avoid errors in measurement, two types of sensors were prepared.…”
Section: The Construction Of Sensorsmentioning
confidence: 99%
“…The procedures of soil preparation, model piles installation, construction of foundations and loading tests were described in our previous paper (Krasiński and Kusio [4]).…”
Section: Examples Of Applicationmentioning
confidence: 99%
“…In terms of model tests, Krasiński and Kusio [14] carried out model tests on group piles and single piles of screw displacement piles (SDPs) and CFA piles and discovered that the load-settlement characteristics were not significantly different in high-density sand. Liu et al [15] examined the differences in the bearing mechanism between SDS piles and CFA piles through sand foundation model tests.…”
Section: Introductionmentioning
confidence: 99%
“…General aspects of ground resistance and PG deformation were analyzed by Adejumo (2013), Broms (1981), Mandolini and Viggiani (1997), Poulos (1968), Randolph (2003) and Vesic (1975). Experimental investigation results were presented by Al-Mhaidib (2006), Kishida (1964), Krasinski and Kusio (2014), McCabe and Lehane (2006), Randolph, Dolwin, and Beck (1994), Sales, Prez-zi, Salgado, Choi, and Lee (2017), Tejchman (1973), Tuan (2016), Vesic (1967Vesic ( , 1968, Q.-q. Zhang, S.-m. Zhang, Liang, Q. Zhang, and Xu (2015).…”
Section: Introductionmentioning
confidence: 99%